TRADISI SEKATEN YOGYAKARTA DALAM PERSPEKTIF KI HAJAR DEWANTARA DAN RELEVANSINYA BAGI PENGEMBANGAN KEBUDAYAAN NASIONAL - Putri, Kusuma; Siswadi, Gede Agus (Dharmasmrti: Jurnal Ilmu Agama dan Kebudayaan, 2024)
The Sekaten tradition is a cultural heritage of the Indonesian nation which until now still exists. Sekaten became an event for the birth of the Prophet Muhammad PBUH which was packaged using Javanese culture. The existence of this Sekaten provides space for culture and religion concurrently. In addition, Sekaten is a way the preservation of the cultural values of the Indonesian nation. Ki Hajar Dewantara's thoughts on culture have revealed this Sekaten tradition, therefore this tradition can survive and thrive amid the challenges of modernization. This research is qualitative research with a literature study approach. The methods used are interpretation, heuristics, and philosophical reflection. The results of this study found that Ki Hajar Dewantara’s thoughts were related to a continuous, convergent, and concentric have relevance to the Sekaten tradition tradition which in its implementation was in accordance with Ki Hajar Dewantara's theory. In addition, national culture in its development process also requires efforts to be able to see culture as prospective and ongoing dynamic process. This sekaten becomes a meeting point between cullture and religion to strengthen the integration of culture that cannot be separated.